2017
DOI: 10.1128/jb.00595-16
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of the Galactitol Utilization Pathway of Salmonella enterica Serovar Typhimurium

Abstract: Galactitol degradation by salmonellae remains underinvestigated, although this metabolic capability contributes to growth in animals (R. R. Chaudhuri et al., PLoS Genet 9:e1003456, 2013, https://doi.org/10.1371/journal.pgen.1003456). The genes responsible for this metabolic capability are part of a 9.6-kb gene cluster that spans from gatY to gatR (STM3253 to STM3262) and encodes a phosphotransferase system, four enzymes, and a transporter of the major facilitator superfamily. Genome comparison revealed the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…3). The molecular excess of protein over DNA for quantitative binding of most promoters tested was in a range between 5 to 21 and thus very low in comparison with other repressors tested under similar conditions1112, pointing to a strong affinity of IolR to its target sequences. The bandshift experiments with the promoters P iolT1 , P iolD1 , P iolR , P iolC1 and P reiD exhibited at least two retarded protein/DNA complexes, suggesting an oligomerization of IolR with increasing protein concentration.…”
Section: Resultsmentioning
confidence: 91%
“…3). The molecular excess of protein over DNA for quantitative binding of most promoters tested was in a range between 5 to 21 and thus very low in comparison with other repressors tested under similar conditions1112, pointing to a strong affinity of IolR to its target sequences. The bandshift experiments with the promoters P iolT1 , P iolD1 , P iolR , P iolC1 and P reiD exhibited at least two retarded protein/DNA complexes, suggesting an oligomerization of IolR with increasing protein concentration.…”
Section: Resultsmentioning
confidence: 91%
“…Additional small horizontally acquired elements involving metabolic genes were identified, including an arsenic resistance island that was found present in all clades of Montevideo [ 46 ]. In addition, a tagatose utilization island tag , which spans STM3251 to STM3256 in Typhimurium [ 47 ], was found but restricted to members of clades I and II ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the apparent niche association of clade I isolates for cattle, and clade II isolates for poultry, it is possible that these metabolic islands contribute to bacterial colonization in livestock. In support of this suggestion, it has been shown that Typhimurium tag operon mutants were markedly attenuated in their ability to colonize the intestines of cattle, swine and poultry [ 47, 83 ], and in serovar Enteritidis, allantoin utilization genes are upregulated in chicken intestines [ 84, 85 ], while allB deletion mutants demonstrate reduced virulence in poultry [ 51 ]. However, further research is needed to understand how these metabolic capabilities actually impact fitness in colonizing livestock.…”
Section: Discussionmentioning
confidence: 99%
“…S. Tm encodes approximately 300 unique sRNAs, and the expression of a subset of sRNAs is highly sensitive to signals encountered within the macrophage environment, such as nutrient starvation, and are controlled by key components of the SPI-2 regulatory system ( Kröger et al, 2012 , 2013 ; Amin et al, 2016 ; Colgan et al, 2016 ). Specifically, the sRNA PinT regulates SPI-2 expression and is critical for host adaptation in vivo ( Chaudhuri et al, 2013 ; Westermann et al, 2016 ). It is possible that post-transcriptional regulation helps S. Tm incorporate environmental signals sensed within the SCV to modulate survival.…”
Section: Intramacrophage Sensing and Signalingmentioning
confidence: 99%